The Biopharmaceutics Risk Assessment Roadmap for Optimizing Clinical Drug Product Performance. Issue 11 (24th September 2014) - Selen, Arzu; Dickinson, Paul A.; Müllertz, Anette; Crison, John R.; Mistry, Hitesh B.; Cruañes, Maria T.; Martinez, Marilyn N.; Lennernäs, Hans; Wigal, Tim L.; Swinney, David C.; Polli, James E.; Serajuddin, Abu T. M.; et al.
<x xml:space="preserve">Abstract</x> The biopharmaceutics risk assessment roadmap (BioRAM) optimizes drug product development and performance by using therapy‐driven target drug delivery profiles as a framework to achieve the desired therapeutic outcome. Hence, clinical relevance is directly built into early formulation development. Biopharmaceutics tools are used to identify and address potential challenges to optimize the drug product for patient benefit. For illustration, BioRAM is applied to four relatively common therapy‐driven drug delivery scenarios: rapid therapeutic onset, multiphasic delivery, delayed therapeutic onset, and maintenance of target exposure. BioRAM considers the therapeutic target with the drug substance characteristics and enables collection of critical knowledge for development of a dosage form that can perform consistently for meeting the patient's needs. Accordingly, the key factors are identified and in vitro, in vivo, and in silico modeling and simulation techniques are used to elucidate the optimal drug delivery rate and pattern. BioRAM enables (1) feasibility assessment for the dosage form, (2) development and conduct of appropriate "learning and confirming" studies, (3) transparency in decision‐making, (4) assurance of drug product quality during lifecycle management, and (5) development of robust linkages between the desired clinical outcome and the necessary product quality attributes for inclusion in the quality target product profile. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3377–3397, 2014